Augustine Tolton’s Struggle as a Black Catholic against Discrimination as Portrayed in From Slave to Priest by Caroline Hamesath and They Called Him Father Gus by Roy Bauer - Agnes Mira Damayanti (Universitas Gadjah Mada, 2017)
This thesis aims to analyze how Black Catholics overcome the discrimination against their life in American society during the nineteenth century and also to explore what are the impacts of Black Catholics struggle portrayed in the biographies entitled From Slave to Priest and They Called Him Father Gus. The interdisciplinary approach applied in this thesis are including literature, sociology, and the concept of time and macro to micro by McDowell are used to enhance the analysis of Black Catholics’ struggle against the discrimination that they got in American society during the nineteenth century.The findings of the thesis show that Black Catholics did some actions to overcome the discrimination against their life in American society. The actions done by Black Catholics are the sign that they work hard struggling against the discrimination from whites, Catholic Church, and Black Protestants. Also, since this thesis highlights the impact of Black Catholics’ struggle, it indicates that the struggle of Black Catholics, represented mostly by the struggle of Father Augustine Tolton, give the positive impacts such as maintaining the good relation among black and white Catholics, inspired Black Catholics to keep struggle for their faith and inspired the establishment of Black Catholics’ organizations. Key words: Black Catholics, Father Augustine Tolton, Struggle, Impacts